HUBUNGAN ANTARA BAURAN PEMASARAN DENGAN MINAT KUNJUNGAN KEMBALI WISATAWAN DI AGROWISATA GUNUNGSARI KOPENG KABUPATEN SEMARANG - Dio Nanda Naibaho; Bayu Nuswantara (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
Agrotourism is a tourist place that utilizes the beauty of natural resources. To increase the number of tourists, companies must highlight their advantages to give satisfaction to tourists. The purpose of the study was to determine the description and relationship of the marketing mix with interest in revisits at Agrotourism Gunungsari Kopeng. This study uses Rank Spearman correlation analysis through interviews using questionnaires of 50 tourists as respondents who were selected through the Non-Probability Sampling Technique. The results show that the interest in revisits is supported by the 4P marketing mix (price, product/service, promotion, place). The results of the correlation analysis of X1 and X2 have a strong and positive correlation rate. They have a significant correlation, while X3 and X4 have a relatively strong and positive correlation rate and havsubstantialcant correlation with interest in revisits (Y).